Entrepreneurship Training for Bajur Village PKK in Developing New Alternative Tourism Potential - Wulandari, Yayang Erry; Rahmat, Mi’rajus Subyan; Hadi, Tama Krisna; Hidayatullah, Heri; Qomariyah, Siti Syafiatul (Abdi Masyarakat, 2024)
Entrepreneurship training activities for the Bajur Village PKK aim to increase understanding and skills in developing local tourism potential and producing cultural-based souvenirs. This training covers entrepreneurial management, including SWOT analysis, business opportunity identification, and tourism product marketing strategies. Participants are trained to exploit local potential and develop small businesses independently with the support of managerial skills and understanding in tourism promotion. Apart from that, the training also focuses on making souvenir products such as pins and key chains, which are easy to make and have high selling value. Assistance is provided to participants during the product making process, accompanied by regular evaluations to ensure the effectiveness of the training. The results of this activity include the creation of new business ideas that can be developed by the Bajur Village PKK as well as increasing capacity in managing businesses based on local tourism potential. The souvenir products produced are ready to be marketed and are expected to be a support in improving the village economy through a sustainable tourism sector.